Analisis Implementasi Kurikulum Merdeka Belajar Pada Siswa-Siswi SMA Negeri 1 Junjung Sirih - Putri Armadani; Putri Kartika Sari; Feri Aldi Abdullah; Merika Setiawan (Peneliti.net, 2023)
In the era of the Covid-19 pandemic in Indonesia, teaching and learning activities were carried out online or face to face. Online learning has significantly changed the learning process for educators and students, resulting in a learning crisis. To overcome this crisis, the government is trying to introduce a new curriculum, namely the independent curriculum or previously the prototype curriculum, introduced from the ministry of education, culture, research and technology (kemendikbudristek). . The way a good independent curriculum works is translating observations into views. Then use the syllabus slowly, after which it is evaluated when problems occur. Therefore, new advances will have an impact on teachers and related agencies. Independent learning is an idea that frees teachers & students to choose learning systems. The goal is based on independent learning, which is to form a fun education for students and teachers because so far education in Indonesia has emphasized aspects of knowledge rather than aspects of skills. Merdekalearning also emphasizes the aspect of character development that is in sync with the values of the Indonesian nation. In the 21st century there are three major competencies, namely the ability to think, act and live in the world. Thinking skills include critical thinking, creative thinking and problem solving. Action skills include communication, collaboration, digital literacy, and technology literacy. Living in the world involves initiative, self-determination, global understanding and social responsibility. These skills must be applied to 21st century learning, a time when innovative and creative people need to adapt quickly. It is important for the government of the Republic of Indonesia to provide adequate facilities and infrastructure as quickly as possible to provide justice for global development. In implementing the independent curriculum, students are required to create or carry out a project. With these project activities, students can develop their skills and potential through various fields. The project activities in this independent curriculum are the only ones using P5 activities. P5 activity is a project activity to strengthen the profile of Pancasila students